INVENTARISASI KANTONG SEMAR (Nepenthes sp) ENDEMIK DATARAN TINGGI KAWASAN TELAGAH PUTERI DELENG PINTAU GUNUNG SIBAYAK KABUPATEN KARO - Syaiful Azhar; Muhammad Iqbal Haitame Tambunan; Irfan Ritonga; Muhajir Syarif Lubis; Dede Kurniawan (Universitas Tanjungpura, 2023)
Data collection of endemic species in each area requires continuous research, aims to determine the existence of the distribution of endemic species in a particular area, one of them is the pitcher plant (Nepenthes sp.). The purpose of this study was to record the species of pitcher plant endemic to the highlands of North Sumatra which are in the Puteri Deleng Pintau Lake area, on Mount Sibayak. The research was conducted from January to February 2022 using an exploratory method. The tools used in this study included soil testers, hygrometers, compasses, GPS, cameras, stationery, observer tables and reference books while the materials were Nepenthes sp plants which were found along the hiking trails. The results of the study found two species endemik to North Sumatra, namely N. tobaica and N. spectabilis. The finding that there is a shift in the habitat findings of N. spectabilis in the Mount Sibayak area has an impact on the threat to the sustainability of this endemic species in nature.Keywords: Endemik, Gunung Sibayak, Nepentheceace, Telagah Puteri AbstrakPendataan spesies endemik pada setiap kawasan memerlukan penelitian berkelanjutan, bertujuan untuk mengetahui keberadaan dari penyebaran spesies endemik pada suatu kawasan tertentu, salahsatunya tumbuhan kantong semar (Nepenthes sp.). Tujuan penelitian ini mendata spesies kantong semar endemik dataran tinggi Sumatra Utara yang berada pada kawasan Telagah Puteri Deleng Pintau tepatnya di Gunung Sibanyak. Penelitian dilakukan pada bulan Januari hingga Februari 2022 dengan menggunakan metode eksploratif. Alat yang digunakan dalam penelitian ini meliputi soiltester, hygrometer, kompas, GPS, kamera, alat tulis, tabel pengamat dan buku referensi sedangkan bahan yaitu tumbuhan Nepenthes sp yang ditemukan disepanjang jalur pendakian. Hasil penelitian ditemukan dua spesies endemik Sumatra Utara yaitu N. tobaica dan N. spectabilis. Temuan bahwa terjadinya pergeseran temuan habitat dari N. spectabilis pada Kawasan Gunung Sibayak yang berdampak pada terancam kelestarian spesies endemik ini di alam.Kata kunci: Endemik, Gunung Sibayak, Nepentheceace, Telagah Puteri